2021
DOI: 10.1186/s40854-021-00253-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and the crude oil market risk: hedging options with non-energy financial innovations

Abstract: This study examines the hedging effectiveness of financial innovations against crude oil investment risks, both before and during the COVID-19 pandemic. We focus on the non-energy exchange traded funds (ETFs) as proxies for financial innovations given the potential positive correlation between energy variants and crude oil proxies. We employ a multivariate volatility modeling framework that accounts for important statistical features of the non-energy ETFs and oil price series in the computation of optimal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…This has hampered stock indices across the world (Jebabli et al, 2021;Sharma et al, 2021a). Furthermore, from the perspective of the commodities market, extant literature attempts to explore the volatility spillover or the causality between the conventional stock markets and commodities markets (Adekoya and Oliyide, 2021a;Li et al, 2021), with a significant focus on oil (Ghorbel and Jeribi, 2021;Salisu and Obiora, 2021) and gold (Sumer and Ozorhon, 2020;Wang and Wang, 2020). Wang and Wang (2020) access the market efficiency of the S&P 500 Index, gold, Bitcoin and US Dollar Index, during the times of the pandemic and conclude that market efficiency decreases the most for S&P500 and the least for Bitcoin, regarding the latter as more resilient than others in times of crisis.…”
Section: Financial Market Interdependencementioning
confidence: 99%
“…This has hampered stock indices across the world (Jebabli et al, 2021;Sharma et al, 2021a). Furthermore, from the perspective of the commodities market, extant literature attempts to explore the volatility spillover or the causality between the conventional stock markets and commodities markets (Adekoya and Oliyide, 2021a;Li et al, 2021), with a significant focus on oil (Ghorbel and Jeribi, 2021;Salisu and Obiora, 2021) and gold (Sumer and Ozorhon, 2020;Wang and Wang, 2020). Wang and Wang (2020) access the market efficiency of the S&P 500 Index, gold, Bitcoin and US Dollar Index, during the times of the pandemic and conclude that market efficiency decreases the most for S&P500 and the least for Bitcoin, regarding the latter as more resilient than others in times of crisis.…”
Section: Financial Market Interdependencementioning
confidence: 99%
“…Including COVID-19 to the list of negative events for stock markets, Topcu and Gulal ( 2020 ) discussed the effects on real oil prices and foreign exchange rate fluctuations caused by COVID-19. Some studies have reported stock market volatility in emerging markets in the Middle East, South America, and Central and Eastern Europe (Anser et al 2021 ; Salisu and Obiora 2021 ). Other studies have mainly focused on the impact of the COVID‑19 outbreak on Chinese‑listed tourism stocks (Wu et al 2021 ), investigation of macroeconomic parameters of Montenegro using a Bayesian VARX approach (Djurovic et al 2020 ) and prevention of crash in stock market as affected by the economic policy uncertainty during the pandemic (Dai et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…COVID-19 sonrasında yaşanan enflasyonist ortam ve akabinde durağanlaşan ekonominin yarattığı zorlu koşullar, bireylerin, sahip oldukları geliri geleceğe değer kaybına uğramadan aktarmalarını mümkün kılacak finansal alternatifleri aramaya yönelmelerine neden olmuştur (Wagner, 2020). Bununla birlikte üretimin azalmasıyla finansal ekonominin reel ekonomi karşısındaki yükselişi, bireysel yatırımcıların tercih edebilecekleri finansal yatırım araçlarının çeşitliliğini artırmıştır (Salisu ve Obiora, 2021). Bu araçlar devlet bünyesinde olabildiği gibi halka açılan özel sektör şirketleri tarafından da oluşturulabilmektedir.…”
Section: Introductionunclassified